BRET biosensors to study GPCR biology, pharmacology, and signal transduction - Salahpour, Ali; Espinoza, Stefano; Masri, Bernard; Lam, Vincent; Barak, Lawrence; Gainetdinov, Raul R. (Frontiers in Endocrinology, 2012)
Bioluminescence Resonance Energy Transfer (BRET) based biosensors have been extensively used over the last decade to study protein-protein interactions and intracellular signal transduction in living cells. In this review, we discuss the various BRET biosensors that have been developed to investigate biology, pharmacology and signalling of G protein-coupled receptors (GPCRs). GPCRs form two distinct types of multiprotein signal transduction complexes based upon their inclusion of G proteins or β-arrestins that can be differentially affected by drugs that exhibit functional selectivity toward G protein or β-arrestin signalling. BRET has been especially adept at illuminating the dynamics of protein-protein interactions between receptors, G proteins, β-arrestins, and their many binding partners in living cells; as well as measuring the formation and accumulation of second messengers following receptor activation. Specifically, we discuss in detail the application of BRET to study dopamine and trace amine receptors signalling presenting examples of an EPAC biosensor to measure cAMP, β-arrestin biosensors to determine their recruitment to the receptor, and dopamine D2 receptor and Trace Amine Associated Receptor 1 (TAAR1) biosensors to investigate heterodimerization between them. As the biochemical spectrum of BRET biosensors expands, the number of signalling pathways that can be measured will concomitantly increase. This will be particularly useful for the evaluation of functional selectivity in which the real time BRET capability to measure distinct signalling modalities will dramatically shorten the time to characterize new generation of biased drugs. These emerging approaches will further expand the growing application of BRET in the screening for novel pharmacologically active compounds.